The Effect of Essential Oil Formulas on Mortality and Oviposition Deterrent of Helopeltis antonii - Tri Lestari Mardiningsih; NFN Ma'mun (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
Citronella, clove and lemongrass oils are known to be toxic and repel certain pests.  Mixing different essential oils (EOs) in the form of formula is expected to increase the insecticidal properties. The experiments aimed to examine the effect of EOs mixture formulas on mortality and oviposition deterrent of Helopeltis antonii. The study was conducted at the green house of Indonesian Spices and Medicinal Crops Research Institute. A mixture of two EOs citronella + clove (1:1), lemongrass + clove (1:1), individual EO formulas, and their inert solution (mixture of tween 80, turpentine, and teepol) were tested on H. antonii at 5 and 10 ml.l-1 concentrations.  Parameters observed were the number of eggs laid, mortality of adults and nymphs of H. antonii. The citronella + clove and lemongrass + clove formula at 10 ml.l-1 deterred the oviposition of  H. antonii by 60.18 % and 46.56 % respectively. These formulas also caused adults mortality at 79.17 % and 62.50 %, as well as the nymphs mortality at 87.50 % and 82.50 % respectively. The citronella + clove and lemongrass + clove formulas tested had the same effectiveness compared to the commercial citronella oil formula. Therefore, these two formulas were potential to be tested in field to control H. antonii.